Temperature Monitoring in PIC Surface - Sushma Pandey; Antonio Teixeira; Mario Lima (Photonics)
In this work we present the extended work of the previously proposed scheme for in-PIC temperature monitoring. This can be used in any photonic integrated circuitry platform, allowing simplified temperature monitoring and improved independence of the interrogating laser wavelength. Theoretically, power sensitivity was observed to be 0.77 dB/°C and 0.98 dB/°C for common mode and differential mode, respectively. The experimentally noted sensitivity of common mode and differential mode are 1.45 dB/°C and 0.8 dB/°C, respectively, at 1524 nm. The scheme allows the monitoring of the average temperature on the surface of the chip, which results from the global effect that affects both gratings (common mode) and the monitoring of the difference in temperature between gratings (differential mode).